2016
DOI: 10.1002/jps.24691
|View full text |Cite
|
Sign up to set email alerts
|

Cocktail-Dosing Microdialysis Study to Simultaneously Assess Delivery of Multiple Organic–Cationic Drugs to the Brain

Abstract: Brain microdialysis is a powerful tool to estimate brain-to-plasma unbound concentration ratio at the steady state (Kp,uu) of compounds by direct measurement of the unbound concentration in brain interstitial fluid. Here, we evaluated a method to estimate Kp,uu values of multiple organic-cationic drugs simultaneously, by means of brain microdialysis combined with cocktail dosing. Five cationic drugs (diphenhydramine, memantine, oxycodone, pyrilamine, and tramadol), substrates of the proton-coupled organic cati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 27 publications
(55 reference statements)
0
26
0
Order By: Relevance
“…Supplemental kinetic study in rodents may facilitate accurate identification of efflux transporters. Recently, it has been reported that the unbound concentrations of several drugs in the brain were greater than in plasma, suggesting the involvement of active influx transporters in brain uptake 20,57 . Conceivably, drugs that are substrates of influx transporters are also not expected to follow the free drug hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Supplemental kinetic study in rodents may facilitate accurate identification of efflux transporters. Recently, it has been reported that the unbound concentrations of several drugs in the brain were greater than in plasma, suggesting the involvement of active influx transporters in brain uptake 20,57 . Conceivably, drugs that are substrates of influx transporters are also not expected to follow the free drug hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo brain microdialysis study in rats was performed by the same methods as described previously. 15,[23][24][25] A microdialysis probe CMA12 (CMA, Stockholm, Sweden) was implanted into the striatum region (2.7 mm lateral and 0.8 mm anterior to the bregma, and 3.8 mm depth from the surface of the parietal bone). Brain microdialysis was performed 48 h after surgery.…”
Section: Brain Microdialysis Studymentioning
confidence: 99%
“…The steady-state concentration of varenicline in the brain ISF was estimated according to the reference method, as reported previously. 15,[23][24][25] For further details, see Supplementary Information.…”
Section: Brain Microdialysis Studymentioning
confidence: 99%
See 1 more Smart Citation
“…It thus appears reasonable to assume that the BBB influx mediated by this transporter is comparable between rat and human, and therefore the human AFs were considered to be similar to rat AFs. The human AF at the BBB, AFin1, was 2.3, which was calculated using a Kpuu,brain ECF (unbound brain ECF -to-plasma concentration ratio) value of 1.7 (Kitamura et al, 2016). The human AFs at the BCSFB, AFout2 and AFout3, were assumed to be 1.9 and 2.3, respectively, which were calculated from a Kpuu,CSF (unbound CSF-to-plasma concentration ratio) value of 1 (Kokki et al, 2014).…”
Section: 322mentioning
confidence: 99%